2022
DOI: 10.1002/admi.202200869
|View full text |Cite
|
Sign up to set email alerts
|

MAB‐Phases and Beyond—A Tribological Success Story?

Abstract: Early transition metal borides (MAB‐phases) are extensively investigated due to their excellent mechanical and tribological properties. These characteristics of ternary transition metal borides have created a promising pathway to achieve strong materials with unique properties. These layered materials combine both metallic and ceramic attributes and possess intriguing properties such as excellent mechanical, chemical, and thermal stability. Most of the MAB‐phases were discovered before the 1990s, but recent di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 82 publications
0
19
0
Order By: Relevance
“…3,4 Previous studies have shown that the selective introduction of Al elements into high-hardness TMB materials to forge what are known as "MAB" phase compounds can effectively improve the fracture toughness and damage tolerance of material systems. 8,9 Moreover, certain MAB phase compounds, owning to their superb resistance to thermal shock 10 and high-temperature oxidation, 11,12 are deemed as prime candidates for fabricating hypersonic aircra and scramjet engines. [13][14][15] Structurally, MAB phase compounds arise from the alternate layering of Al atomic layers and TMB layers: [9][10][11][12] within the TMB layers, robust B-B bonds (typically <2 Å) and TM-B bonds (typically ∼2 Å) coexist, whereas the bonds linking the TMB layers and Al layers, such as TM-Al and Al-B bonds (typically >2 Å), exhibit comparatively lower strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Previous studies have shown that the selective introduction of Al elements into high-hardness TMB materials to forge what are known as "MAB" phase compounds can effectively improve the fracture toughness and damage tolerance of material systems. 8,9 Moreover, certain MAB phase compounds, owning to their superb resistance to thermal shock 10 and high-temperature oxidation, 11,12 are deemed as prime candidates for fabricating hypersonic aircra and scramjet engines. [13][14][15] Structurally, MAB phase compounds arise from the alternate layering of Al atomic layers and TMB layers: [9][10][11][12] within the TMB layers, robust B-B bonds (typically <2 Å) and TM-B bonds (typically ∼2 Å) coexist, whereas the bonds linking the TMB layers and Al layers, such as TM-Al and Al-B bonds (typically >2 Å), exhibit comparatively lower strength.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Previous studies have shown that the selective introduction of Al elements into high-hardness TMB materials to forge what are known as “MAB” phase compounds can effectively improve the fracture toughness and damage tolerance of material systems. 8,9 Moreover, certain MAB phase compounds, owning to their superb resistance to thermal shock 10 and high-temperature oxidation, 11,12 are deemed as prime candidates for fabricating hypersonic aircraft and scramjet engines. 13–15…”
Section: Introductionmentioning
confidence: 99%
“…The MAB phases consist of atomically layered ternary or quaternary transition metal (M) borides, described by the general formula (MB) 2 z A x (MB 2 ) y ( z = 1–2; x = 1–2; y = 0–2). These phases have structures composed of transition M–B sublattices interleaved by mono- or bilayers of A atoms (A = Al, Zn) and have garnered attention due to their unique properties, finding applications in catalysis, electronics, coatings, and energy storage. These materials are known for their high electrical conductivity, thermal stability, and resistance to oxidation, making them suitable for ultrahigh-temperature applications demanding corrosion resistance . Oxidation resistance in MAB phases relies on the development of dense oxide layers like Al 2 O 3 and Cr 2 O 3 , acting as barriers to elemental diffusion .…”
Section: Introductionmentioning
confidence: 99%
“…Such means have been extended to the investigations of layered transition metal boride (MAB) phases 35 and the successful synthesis of Mbenes. 36 It may also enlighten the exploration and realization of new monoelemental 2D boron phases.…”
Section: Introductionmentioning
confidence: 99%